Social Relationship Prediction Integrating Personality Traits and Asymmetric Interactions - Ju, Chunhua; Li, Geyao; Bao, Fuguang; Gao, Ting; Zhu, Yiling (Frontiers in Psychology, 2022)
Social networks have become an important way for users to find friends and expand their social circle. Social networks can improve users' experience by recommending more suitable friends to them. The key lies in improving the accuracy of link prediction, which is also the main research issue of this paper. In the study of personality traits, some scholars have proved that personality can be used to predict users' behavior in social networks. Based on these studies, this paper aims to improve the accuracy of link prediction in directed social networks. Considering the integration of personality link preference and asymmetric interaction into the link prediction model of social networks, a four-dimensional link prediction model is proposed. Through comparative experiments, it is proved that the four-dimensional social relationship prediction model proposed in this paper is more accurate than the model only based on similarity. At the same time, it is also verified that the matching degree of personality link preference and asymmetric interaction intensity in the model can help improve the accuracy of link prediction.